Peluang Dan Tantangan SDM Bali Serta Strategi Dalam Menyambut Kegiatan Presidensi G20 - Ni Putu Diah Mustika Yanthi; Ni Made Yudhaningsih; I Made Anom Arya Pering (CV ODIS, 2022)
This study aims to examine and analyze the role of the Opportunities and Challenges of Bali's Human Resources in Welcoming the Activities of the G20 Presidency. This study uses data collection techniques with the method of observation, interviews, and documentation. The data analysis technique used in this research is descriptive analysis. The results of this study indicate that (1) The opportunities generated from the activities of the G20 Presidency can create economic cycles both micro and macro that are more significant than before. Moreover, the province of Bali in this case being the venue for the peak event of the G20 Presidency will be able to boost the existence of Bali tourism in the eyes of the world. (2) The challenge that will be faced by Bali's HR is competition with foreign workers which can suppress local HR job opportunities. (3) The strategy that must be used in taking advantage of opportunities and responding to challenges is to improve the quality of human resources, open up more economic sectors for investment, prepare economic and industrial infrastructure, and improve national education. as possible and able to compete with other countries.